2019
DOI: 10.1155/2019/2517293
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Biochemical Biodiversity of Camel Milk

Abstract: Due to its balanced composition in basic nutrients, its richness in vitamins and in minerals, camel milk has a special place in the daily diet of southern populations. The present study aimed at examining some physicochemical and biochemical characteristics of camel milk (Camelus dromedarius) in Morocco. To achieve this aim, three batches of samples of camel milk were collected from various regions (Dakhla, Errachida, and Fès-Meknes) undergoing physicochemical and biochemical analyses. Results showed that Moro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(25 reference statements)
4
13
0
Order By: Relevance
“…Finally, the mean value of fat content in both areas were similar. These results are in harmony with those of Bouhaddaoui et al (2019). It could be observed that, the mean values of acidity determined as lactic acid was 0.16% in samples collected from A1, while the mean values of acidity in the samples collected from A2 was 0.18%.…”
Section: Chemical Composition Of Camel Milksupporting
confidence: 86%
“…Finally, the mean value of fat content in both areas were similar. These results are in harmony with those of Bouhaddaoui et al (2019). It could be observed that, the mean values of acidity determined as lactic acid was 0.16% in samples collected from A1, while the mean values of acidity in the samples collected from A2 was 0.18%.…”
Section: Chemical Composition Of Camel Milksupporting
confidence: 86%
“… 1 FAO ( 2020b ) 2 Egg—Sun et al ( 2019 ) 3 Egg—Sun et al ( 2019 ); cow milk—Franzoi et al ( 2019 ); buffalo milk—Mohamed et al ( 2011 ); sheep and goat milk—Ferro et al ( 2017 ); camel milk—Bouhaddaoui et al ( 2019 ) …”
Section: Methodsmentioning
confidence: 99%
“…Both water-soluble and fat-soluble vitamins are found in all animals' milk. Camel milk is a kind of exception because of its high concentration of vitamin C. It contains 3 to 5 times more vitamin C (3.0 to 7.5 mg/100 g) than cow's milk (0.8 to 2 mg/100 g), whereas vitamin C concentration is relatively close to that of human milk (1.19 to 7.84 mg/100g) with an average 4.86 mg/100 g [22,52]. Likewise, camel milk exhibited high levels of vitamin B1, B12, folic acid and pantothenic acid than cow's milk [50].…”
Section: Vitaminsmentioning
confidence: 99%